Perancangan Sistem Informasi Manajemen Sekolah dalam Penerapan Smart School untuk Meningkatkan Efisiensi Administrasi dan Pembelajaran Menggunakan Metode CRM (Customer Relationship Management) di Waransansart Lammai School - Anggi Irana Bela; Al-Khowarizmi Al-Khowarizmi (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
Waransansart Lammai School, an Islamic school in Yala, Thailand, faces challenges in implementing Smart School due to manual administration and limited teacher digital literacy. This research aims to analyze existing conditions, design a web-based School Management Information System (SIMS) with CRM integration, measure digitalization impact over 30 days KKN, and develop system concepts. Using qualitative descriptive approach with quantitative measurements, the population comprises school principal, teachers, and staff, selected via purposive sampling. Instruments include observation guidelines, semi-structured interviews, and documentation sheets, analyzed through Miles & Huberman's model and descriptive statistics. Results show 58.31% time efficiency improvement (from 49.97 to 20.83 minutes daily) and error rate reduction to 3.75%. CRM implementation enhances operational, analytical, and collaborative processes. The study concludes that SIMS with CRM significantly boosts administrative efficiency and stakeholder communication in Smart School framework.